2008
DOI: 10.1177/0192623307311400
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Laser Capture Microdissected Rat Arterial Elements: Fenoldopam-induced Vascular Toxicity as a Model System

Abstract: Transcriptional profiling of specific elements of vasculature from animal models of vascular toxicity is an approach to gain insight into molecular mechanisms of vascular injury. Feasibility of using laser capture microdissection (LCM) to evaluate differential gene expression in selected elements of mesenteric arteries (MA) from untreated rats and rats given a single vasotoxic dose of 100 mg/kg Fenoldopam and euthanized 1 or 4 hours postdose was assessed. Regions of MA (endothelial cells [EC] and vascular smoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…The mesentery tissue was rinsed with saline (NaCl 0.9%) and then rolled onto the plunger of a 1-cc syringe; the rolled tissue was placed in a small tissue cassette and fixed in 10% formalin for 24 hr prior to embedding in paraffin. The tissue was sectioned at 5 μm and stained with H&E. Dalmas et al (2008) excised the entire mesentery, removed the mesenteric lymph, and cut in half the mesentery. Each half was rolled on a 3-mm-diameter plastic cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…The mesentery tissue was rinsed with saline (NaCl 0.9%) and then rolled onto the plunger of a 1-cc syringe; the rolled tissue was placed in a small tissue cassette and fixed in 10% formalin for 24 hr prior to embedding in paraffin. The tissue was sectioned at 5 μm and stained with H&E. Dalmas et al (2008) excised the entire mesentery, removed the mesenteric lymph, and cut in half the mesentery. Each half was rolled on a 3-mm-diameter plastic cylinder.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not validate the translational statin response in the in vivo cynomolgus macaque because of time and cost constraints, we did perform a similar study where we validated the translation drug response of fenoldopam in rats with our rat vascular surrogate system and demonstrated similar responses. [44][45][46] Finally, we have found that certain biological pathways that may explain statin effects on other tissues, such as skeletal muscle, are conserved in our vascular tissue. Thus, many of the effects observed in the vascular system potentially may be translated to other organ systems.…”
Section: Table 3 Summary Of Gene Mutations That Lead To Muscle Pathomentioning
confidence: 99%
“…Kerns et al 2005; C. Louden et al 2006;Newsholme et al 2000;Stagliano et al 2001;Thomas et al 2009;Thomas et al 2012;Turk 2010;Weaver et al 2008;Zhang et al, 2002b;Zhang et al 2006;2012). The majority of candidate biomarkers have included factors involved in EC activation , edema, inflammation, tissue remodeling, (Blake, and Ridker 2001;Dalmas et al 2008;Daguès, Pawlowski, Guigon, et al 2007;) and maintenance of vascular tone (C. Louden et al 2006). The search for DIVI markers has been formalized, with the formation of a collaborative consortium of industry, academic, and regulatory experts into The Predictive Safety Testing Consortium (PSTC) Vascular Injury Working Group (VIWG), and a panel of biomarkers for DIVI has been proposed (Mikaelian et al 2014).…”
Section: Biomarkers Of Biotherapeutic-associated Divimentioning
confidence: 99%